Study of Electrically Conductive Polymer for Antistatic and Sensor Application - Anita Gaur*; Niharika (International Journal of Minerals, 2026)
Electrically conductive polymers (ECPs) are a unique category of smart materials that integrate the mechanical flexibility and ease of processing characteristic of conventional polymers with the electrical conductivity typically associated with metals or semiconductors. In recent years, they have attracted considerable interest due to their promising potential in advanced technological applications, especially in antistatic coatings and electronic sensing devices. The unique ability of these polymers to conduct electricity arises from their conjugated molecular structure, which allows for the elocalization of It-electrons along the polymer backbone. Common examples include polyaniline (PANI), polypyrrole (PPy), and polythiophene (PT), each exhibiting tunable electrical properties depending on their hemical structure, doping level, and processing methods. In antistatic applications, conductive polymers help to safely dissipate unwanted static charges from surfaces, protecting sensitive electronic devices, preventing dust attraction, and reducing the risk of ignition in flammable environments. Unlike traditional antistatic materials that rely on surface additives, ECPs provide long-lasting and more reliable static protection due to their intrinsic conductivity. In the field of sensing, conductive polymers are widely used in chemical, biological, and physical sensors due to their sensitivity to changes in their environment. They can respond to stimuli such as temperature, p1-I, gas concentrations, or mechanical stress by changing their electrical properties, making them ideal for flexible, wearable, and low-cost sensing platforms. The interaction between the polymer and the target analyte often leads to changes in conductivity, which can be easily measured and analyzed. This project explores the underlying principles of conductivity in polymers, the methods used to synthesize and modify them, and the ways in which their properties can be tailored for specific applications. It also highlights recent developments and challenges in the field, aiming to provide a comprehensive understanding of how conductive polymers are shaping the future of smart materials in antistatic and sensor technologies.
Keywords: Doped; Electrically Conductive Polymers (ECPs); Polymers; Polypyrrole; Semiconductors